2017
DOI: 10.2147/ott.s133917
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of adding induction chemotherapy to concurrent chemoradiotherapy for stage T3N0-1 nasopharyngeal carcinoma: a propensity-matched study

Abstract: ObjectiveOur objective was to examine whether adding induction chemotherapy to concurrent chemoradiotherapy improved survival in stage III nasopharyngeal carcinoma (NPC) patients, especially in low-risk patients at stage T3N0-1.Materials and methodsWe retrospectively analyzed 687 patients with stage T3N0-1 NPC treated with intensity-modulated radiation therapy (IMRT) plus concurrent chemotherapy (CC) with or without induction chemotherapy (IC). Propensity score matching (PSM) method was used to select 237 pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…In the present study, the overall incidence of grade 3 acute toxic effects was higher in the IMRT/chemotherapy group than in the IMRT-only group; significantly higher incidence was seen of grade 3 leukopenia/neutropenia, nausea/vomiting, and mucositis. Some earlier studies have reported similar findings [7,13]. We separated the patients into different subgroups according to various baseline factors.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the present study, the overall incidence of grade 3 acute toxic effects was higher in the IMRT/chemotherapy group than in the IMRT-only group; significantly higher incidence was seen of grade 3 leukopenia/neutropenia, nausea/vomiting, and mucositis. Some earlier studies have reported similar findings [7,13]. We separated the patients into different subgroups according to various baseline factors.…”
Section: Discussionmentioning
confidence: 61%
“…Second, the high frequency of severe adverse reactions in patients treated with IMRT/chemotherapy may have masked any survival benefit in this group [17]. Lan et al have also found that addition of chemotherapy to IMRT does not significantly improve OS; additionally, the authors reported that the higher the incidence of grade 3-4 acute toxicities (especially hematological events such as leucopenia and neutropenia [13]) increases the possibility of discontinuation of treatment. Thus, it seems that IMRT alone may be more suitable than CCRT for patients with stage II and T3N0M0 NPC.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, several clinical trials have provided evidence that IC before definitive CCRT is associated with lower incidence of distant metastases and further improved patient survival (7,18,19). However, according to studies among patients with stage T3-4 N0-1, clinical outcome was similar between the CCRT and IC + CCRT groups, indicating that IC might benefit only patients with a greater tumor burden (9,10). Considering the toxicity and economic cost of chemotherapy, it is important to identify suitable patients who could benefit from additional IC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, not all patients with locoregionally advanced NPC benefit from IC. Previous studies have reported that IC might not improve survival among patients with T3-4N0-1 NPC; in fact, IC has been associated with severe toxicity in this patient group (9,10). Given the body of evidence, it is likely that patients at high risk might benefit from IC more than patients at low risk.…”
Section: Introductionmentioning
confidence: 90%
“…Consequently, IC has been routinely recommended for advanced NPC. However, it should be pointed out that the advanced disease consisted of many subgroups and not all of them could benefit from additional IC (10,11). Thus, identifying the high-risk subgroups who could benefit from IC is the key to improve management of advanced NPC.…”
Section: Introductionmentioning
confidence: 99%